Study on Groundwater-Recharge Test for Deep Excavation of Subway Station in Water-Rich Sandy Strata - LI Weihua; LIU Tianren; HONG Xiaoxing; JING Xucheng; TAN Yong (Nantong Daxue xuebao. Ziran kexue ban)
Water-rich sandy strata have the characteristics of large permeability coefficient, high water content, and poor self-stability, which make it difficult for safe construction of urban deep excavation. Especially in the water-rich and sandy strata where the aquitard is missing, the dewatering of excavation is more likely to trigger engineering disasters, which is a difficult problem in the field of underground engineering. Aiming at the geological conditions of water-rich sandy geological conditions, based on the field groundwater-recharge test at a subway station in Nantong, this study probes into the duration process of water level change, settlement change and the influence of pumping and recharge on surrounding ground subsidence. The test results show that: 1) Although the aquitard is missing, the hydraulic connection between the upper soil layers((3)2-silt and(3)4-fine silt) is more closely related, and the connection with the lower soil layer((6)-silt) is weak; 2) The surface subsidence caused by dewatering is lagging; 3) After the pumping is stopped, the water level recovers fast. The surface subsidence and the deep soil subsidence both rebound to some extent; 4) After the surface subsidence caused by dewatering stabilizes, it is difficult to recover the plastic subsidence in a short time after recharge measures are taken. Therefore, an integrated pumping and irrigation scheme should be adopted to control subsidence. The relevant test results can provide a reference for the future related projects.